Grit and Meaning in Life of Chinese Nurses: The Chain Mediating Effect of Social Support and Hope - Yang, Lei; Wu, Dongmei (Frontiers in Psychology, 2021)
Grit, defined as perseverance and passion for long-term goals, may affect the stability of nursing workforce and nurses’ physical and mental health continuously. Meaning in life has received considerable attention from scholars, which is an important component in positive psychology. This study aimed to delve into the relation between grit and the meaning in life of Chinese nurses. Additionally, we also seek to prove the chain mediating effect of social support and hope on this relationship. An online questionnaire survey was used to collect data from 704 Chinese nurses from general and psychiatric hospitals using the self-made demographic questionnaire with Short Grit Scale, The Perceived Social Support Scale, Adult Dispositional Hope Scale, and Meaning in Life Questionnaire. Moreover, SPSS 25.0 was applied for multiple linear regression, Process v 3.3 plug-in SPSS 25.0 was used for testing the mediation effect between variables. Results showed a strong positive relationship between grit and meaning in life and verified the mediating effect of social support, and hope on grit and meaning in life. The results also confirmed the chain mediating model between grit, social support, hope, and meaning in life.